Necropolis - Khodasevich, V. F. (Vladislav Felit͡sianovich), 1886-1939 (Russian library, 2019)
Necropolis is an unconventional literary memoir from Vladislav Khodasevich, hailed by Vladimir Nabokov as "the greatest Russian poet of our time." In each of the book's nine chapters, Khodasevich memorializes a significant figure of Russia's literary Silver Age, and in the process writes an insightful obituary of the era.